Modelling textile structures using bicontinuous surfaces. Issue 4 (1st October 2020) - Knittel, Chelsea E.; Tanis, Michael; Stoltzfus, Amy L.; Castle, Toen; Kamien, Randall D.; Dion, Genevieve
Abstract : We present a method for modelling textile structures, such as weft knits, on families of bicontinuous surfaces. By developing a tangible interpretation of mathematical theory, we combine the perspectives of art, design, engineering, and science to understand how the architecture of the knit relates to its physical and mathematical properties. While modelling and design tools have become ubiquitous in many industries, there is still a significant lack of predictive advanced manufacturing techniques available for the design and fabrication of textiles. We describe a mathematical structure and the building of a physical prototype to demonstrate a system for dynamic modelling of textiles, including post-fabrication changes in size and shape due to yarn relaxation. This tool may be used to inform and predict relevant textile parameters prior to fabrication and to streamline production of knit textiles for industry, makers and textile artists. GRAPHICAL ABSTRACT: UF0001